Avaliação da perda sanguínea em gestantes submetidas à indução do parto com misoprostol - Sousa, Paulo César Praciano de (2009)
to evaluate the blood loss in induced vaginal delivery by misoprostol and caesarians section with induction attempt, through the hemoglobin blood levels pre and post delivery. To evaluate the blood loss in spontaneous vaginal deliveries and elective caesarians through the hemoglobin blood levels pre and post delivery. To compare the blood loss, evaluated by the hemoglobin blood levels pre and post delivery between induced and non induced deliveries. Subjects and methods: this study included 101 pregnant women admitted to the Assis Chateaubriand Maternity School of the Federal University of Ceará which met the criteria for induced delivery labor. Patients were submitted to transabdominal obstetric ultrassound for evaluation of the static and fetal weight and amniotic liquid index, and basal cardiotocography in order to evaluate fetal vitality. Procedures were taken for induced labor delivery with misoprostol 25mcg, by vaginal rout. The pills were administered each 6 hours in a maximum number of six. The control group was formed by 30 patients that initiated labor spontaneously and 30 patients that achieved caesarians electively. The statistical analysis was done with the program SPSS10.0 (SPSS Co, Chicago, IL, USA). The data were described through the medium, standard deviation, median, minimum, maximum, absolute (n) and relative (%) frequencies. The tests used for comparison of media: T of student; of median: Mann-Whitney, Qui-square or Exact of Fisher; and the Coefficient of Spearman correlation. The evaluation of hemoglobin levels before and after delivery was analyzed through the ANOVA test for repeated values, taking in account the effect of time (pre and post delivery) and the effect of the group (with and without the use of misoprostol). Results: there was a statistically significant difference between time in both types of delivery (p<0.0001).There were no statistical significance between the groups (p>0.05). Additionally, there was a similar pattern of decrease in hemoglobin blood levels pre and post labor in both groups evaluated, in the caesarian delivery (p=0.6845) and normal delivery as well (p=0.2694). Conclusions: labor induction with misoprostol does not modify the blood loss during induced vaginal deliveries and caesarians section with induction attempt, when compared to, respectively, the blood loss in spontaneous vaginal deliveries and in elective caesarians.